(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2025)
This paper aims to explore the potential of activating Al-Khrouba Road in the city of Misurata as a multifunctional urban space that promotes social interaction and cultural diversity, through the integration of universal design principles and the concept of the shared street. The research adopts a mixed analytical methodology that includes urban, social, and field analysis in order to understand the current characteristics of the street and diagnose deficiencies in infrastructure and user behavior. The analysis revealed functional and spatial gaps that have affected the streets ability to fulfill its social and cultural role. As a result, the study proposes a distribution of new community buildings and activities along the street, connected to the sidewalk through interactive seating areas and tree-shaded walkways. These elements contribute to reorganizing and balancing human activity across the space, enhancing the streets flexibility and encouraging interaction among diverse social groups –especially when religious, social, cultural, and educational activities are integrated in a participatory manner. This study contributes to the planning and repurposing of urban open space and the redesign of public streets to create a more inclusive and sustainable urban environment. It redefines the sidewalk as an interactive domain that strengthens community identity and responds to contemporary life needs.